Commercial Slit Lamp Anterior Segment Photography versus Digital Compact Camera Mounted on a Standard Slit Lamp with an Adapter. (3rd October 2018) - Oliphant, Huw; Kennedy, Alasdair; Comyn, Oliver; Spalton, David J.; Nanavaty, Mayank A
ABSTRACT: Purpose: To compare slit lamp mounted anterior segment cameras (SLCs) versus digital compact camera (DCC) with slit-lamp adaptor when used by an inexperienced technician. Methods: In this cross sectional study, where posterior capsule opacification (PCO) was used as a comparator, patients were consented for one photograph with SLC and two with DCC (DCC1 and DCC2), with a slit lamp adaptor. An inexperienced clinic technician, who took all the photographs and masked the images, recruited one eye of each patient. Images were graded for PCO using EPCO 2000 software by two independent masked graders. Repeatability between DCC1 and DCC2, and limits-of-agreement between SLC and DCC1 mounted on slit-lamp with an adaptor were assessed. Coefficient-of-repeatability and Bland-Altmann plots were analyzed. Results: Seventy-two patients (eyes) were recruited in the study. First 9 patients (eyes) were excluded due to unsatisfactory image quality from both the systems. Mean evaluation of posterior capsule opacification (EPCO) score for SLC was 2.28 (95% CI: 2.09–2.45), for DCC1 was 2.28 (95% CI: 2.11–2.45), and for the DCC2 was 2.11 (95% CI: 2.11–2.45). There was no significant difference in EPCO scores between SLC vs. DCC1 ( p = 0.98) and between DCC1 and DCC2 ( p = 0.97). Coefficient of repeatability between DCC images was 0.42, and the coefficient of repeatability between DCC and SLC was 0.58. Conclusions: DCC on slit lamp with an adaptor is comparable to a SLC. There is an initial learning curve, which is similar for both for an inexperienced person. This opens up the possibility for low cost anterior segment imaging in the clinical, research, and teaching settings.